Power System State Estimation with Optimal PMU Placement under Contingencies - Sah, Rupesh Kumar; Adhikari, Yuba Raj; Pankaj, Prabhat Kumar (International Journal on Engineering Technology, 2024)
It discusses the significance of Phasor Measurement Units (PMUs) in monitoring and protecting power systems. DC load flow method is used to analyze power flow in electrical networks, assuming certain conditions like Constant voltage magnitudes and steady-state analysis. It introduces a novel algorithm for optimal PMU placement based on maximum connectivity considering both normal and contingency conditions. Additionally, a new state estimation algorithm is presented for estimating the system states (Voltage magnitude and angle) by minimizing the weighted least-square problem with respect to x. The effectiveness of the algorithms is demonstrated through testing on various bus test systems, showcasing their suitability for practical applications in power system monitoring.